Answer:
<h3>12√6</h3>
Step-by-step explanation:
Given the expression;
2√3 * 3√√8
= (2*3) * (√3*√8)
= 6 * (√24)
= 6 * √4*6
= 6 * (2√6)
= (6*2)√6
= 12√6
Hence the simplified form of the expression is 12√6
Answer:
1.1000
2.3/4
3.f(x)=1000(1/4)^X
Step-by-step explanation:
Answer:
Answer C
Step-by-step explanation:
The rules of logarithmic functions require the two log functions to have the same base. If they do not have the same base, you cannot apply any of the rules.
C
1yd^2 = 9ft^2
_____yd^2 = 2700ft^2
2700 / 9 = 300 yd^2